2019
DOI: 10.18203/2320-6012.ijrms20191079
|View full text |Cite
|
Sign up to set email alerts
|

Study of prosthetic heart valve thrombosis and outcomes after thrombolysis

Abstract: Background: The study aimed to evaluate the clinical presentation, diagnostic features, treatment strategies, and complications of prosthetic heart valve thrombosis (PHVT) and to determine efficacy, outcomes and complications of thrombolytic therapy during hospital stay.Methods: This was a prospective, observational, single-centre study carried out between March, 2016 and December, 2017 at a tertiary care centre in India. Total 110 patients with history of prosthetic heart valve replacement and symptoms relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
2
3
0
Order By: Relevance
“…In our study, 82.86% of the patients either had suboptimal INR or poor compliance with oral warfarin therapy. Similar results were found in another study in which 55.50% of the patients had suboptimal INR and 20.90% of the patients were non-compliant with warfarin therapy [10]. The reason being female predominance of patients (58.50%) who are usually lost to follow-up after replacement resulting in suboptimal INR and poor compliance with warfarin.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, 82.86% of the patients either had suboptimal INR or poor compliance with oral warfarin therapy. Similar results were found in another study in which 55.50% of the patients had suboptimal INR and 20.90% of the patients were non-compliant with warfarin therapy [10]. The reason being female predominance of patients (58.50%) who are usually lost to follow-up after replacement resulting in suboptimal INR and poor compliance with warfarin.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, PVT was more common in women (51.8%) which is similar to the previous studies conducted in India showing that women have been more susceptible to PVT. 12 The results of this study support the findings of 13,14 Parallelly many studies have confirmed that occurrences of mitral PVT have been 2-3 times greater than with aortic PVT. 6,15 Besides, the majority of the patients in this study population have mechanical valve involvement than bioprosthetic valves and also higher number of patients had NYHA class II symptoms followed by III and IV symptoms which were similar to a study conducted by Patil S, et al 13 Streptokinase (87.5%) was the most commonly administered agent for thrombolysis followed by urokinase (10.7%) and tenecteplase (1.8%).…”
Section: Discussionsupporting
confidence: 83%
“…8 Patil et al and Gupta et al showed that mitral valve prosthesis was most commonly involved in the patients (71.5%) compared to aortic valve prosthesis (19.6%). 9,10 Diagnosis is often confirmed by fluoroscopy or echocardiography. Although TTE is used for calculation of gradient and response to thrombolytic therapy, definitive diagnosis is greatly aided by TEE, particularly three-dimensional echocardiography.…”
Section: Discussionmentioning
confidence: 99%